Peran Guru Dalam Implementasi Pendidikan Karakter Sekolah SMP Islam Manbaul Hikmah Luwungragi Brebes - Widya Agustin; Astuti Darmiyanti (Peneliti.net, 2023)
The education that is currently implemented in various schools is character education which cannot be separated from the role of teachers and school members to support the achievement of character education. The Role of the Teacher in Implementing Character Education in Schools is the subject of discussion in writing this research. The purpose of this research is to find out how far the teacher plays a role in implementing character education and to find out the obstacles faced by teachers in implementing character education. The method used in this study is a qualitative method with data collection methods namely observation, interviews, and documentation. The research subjects were teachers and school principals. Data analysis used data presentation, data reduction and conclusion. Data validity extends the observation period, continuous observation, and triangulation. The application or implementation of character education to students is inseparable from the role of the teacher, because the teacher is essentially an educator, teacher, advisor, role model, and motivator for students. Obstacles faced by teachers in implementing character education, among others. a) The geographical location of the school is far from where the students live, so that it can hamper the process of carrying out learning and extracurricular activities, b) The educational level of parents of students is still very low, it can hinder the implementation of character education, because parents are only silent and surrender education completely to the teachers and they do not realize that the role of parents is very helpful in achieving these goals, and c) Lack of knowledge and understanding of students about character education, because with the knowledge of students it really supports the achievement of character education which is given at any time in the learning process , because it is difficult to implement and even provide understanding to students if they themselves cannot understand what character education is, its purpose, and what are the benefits for them, both in the school environment and the community environment.